Effect of Switching Frequency in DTC Based Switched Reluctance Motor Drive - Srinivas Pratapgiri (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Since the magnetizing characteristics are highly non-linear in nature, the torque ripple is high in the Switched Reluctance Motor (SRM). The torque ripple can be minimized by using a novel control technique called Direct Torque Control (DTC). In DTC technique, torque is controlled directly through control of magnitude of the flux-linkage and change in speed of the stator flux vector. The flux and torque are maintained within set hysteresis bands. This paper analyzes performance of the DTC based drive mainly in terms of the torque ripple in MATLAB/SIMULINK environment and results are discussed elaborately. The paper also analyzes the effect of these two bands on switching frequency of the converter. http://dx.doi.org/10.11591/telkomnika.v12i12.6718